S06. A case of linear scleroderma en coup de sabre and epilepsy: Manage the sabre to control the seizures. (May 2018) - Gregg, Nicholas M.; Osborn, Thomas G.; Kotsenas, Amy L.; Britton, Jeffrey; Cascino, Gregory D.
Abstract : Introduction: Linear scleroderma en coup de sabre (ECS) is a rare form of localized scleroderma (0.4–2.7/100, 000 people) (Peterson et al., 1997 ) that has characteristic cutaneous involvement of the forehead and scalp (Holland et al., 2006 ) and is named in reference to its "stroke of a sabre"-like appearance. It typically has onset in the pediatric population and has a higher association with extracutaneous manifestations than other forms of localized scleroderma. Focal epilepsy is the most commonly reported extracutaneous manifestation of ECS, seen in 42% of reported cases (Doolittle et al., 2015 ). In one study, 7 of 7 patients with ECS associated epilepsy had abnormal brain imaging (Amaral et al., 2013 ). Methods: Ms. J is a 24 year old right handed woman with history of ECS diagnosed in 2007 involving the left forehead, refractory left temporal lobe epilepsy with onset in 2008, and a left anterior temporal lobe lesion that was resected in 2008 with reported pathology of arteriovenous malformation (AVM). Ms. J has undergone extensive evaluation by physicians in the departments of neurology and rheumatology at the Mayo Clinic since 2013, including two epilepsy monitoring unit (EMU) evaluations, ictal-SPECT scan, serial brain MRI and head and neck MRA studies, serological testing, and CSF testing. She has been treated with various antiepileptic medications, and methotrexate and mycophenolate mofetil have been used to manage her ECS. Results: Preoperative imaging of the left anterior temporal lobe lesion was retrospectively reviewed by the Mayo Clinic neuroradiology department and is not suggestive of AVM; request for pathology slides from the outside facility has been unsuccessful. Serial imaging since the resection shows new T2 hyperintensity, microhemorrages on susceptibility sequences, and scattered enhancement in the mid and posterior left temporal region, identical in appearance to the resected anterior temporal lobe lesion. Ms. J enjoyed 2 extended periods of seizure freedom, 2008 – May, 2011, and November, 2013 – November, 2016. Her seizure control correlated with treatment of her ECS: she reliably took methotrexate from 2008 – February, 2011 and mycophenolate mofetil from September, 2013 – August, 2016. She restarted mycophenolate mofetil in Jaunary, 2017 and has been seizure free since July (except for an EMU admission October, 2017 on reduced antiepileptic medications). She has been treated with a combination of lamotrigine, levetiracetam, and oxcarbazepine, currently all three, and was maintained on antiepileptic medications since 2008. Conclusion: This case illustrates the importance to recognize ECS as a cause of focal epilepsy and brain imaging lesions, and suggests a need for ECS management for seizure control. Proper diagnosis is needed to avoid ineffective brain surgery and to prompt appropriate ECS treatment.